Transforming electronic waste into sustainable building materials for a cleaner environment: a review - M. Vishnu Priyan; Durga Prasad Ravella; George Uwadiegwu Alaneme (Discover Materials)
Abstract The exponential rise in the manufacturing of electronic components due to technological innovation and the resulting spike in e-waste have prompted scientists and researchers to seek new and sustainable methods to reuse/recycle e-waste to limit its detrimental impact on the environment. Recycling e-waste is still a challenging process due to the lack of facilities. Moreover, disposing of the massive amount of e-waste poses an insurmountable difficulty owing to the presence of toxic chemicals. The enormous output of e-waste has produced many complications, leading to treatment alternatives and detrimental effects on human health and the environment. Most developed countries possess viable e-waste management technology, technological expertise, and well-defined system boundaries. However, the situation differs in underdeveloped countries due to various problems and a lack of applicable policies. Recycling electronic trash into construction materials has significant potential for decreasing waste management issues and safeguarding the environment from contamination. This article summarizes the potential uses of e-waste in building materials through numerous studies utilizing a scientometric approach. A broad spectrum of data has been studied, and the mechanical and durability characteristics of concrete containing e-waste have been compared. This would prove beneficial to the research community, where one can predict the trends in the variation in mechanical characteristics with different replacement percentages of fine and coarse aggregates. E-waste can be used as an effective alternative material to natural aggregates.